ESTUDIO COMPARATIVO DE LOS DIVERSOS MEDIOS DE CUANTIFICACION DE LA JUVENTUD LINFOCITARIA - GONZALEZ GUZMAN, IGNACIO (Instituto Politécnico Nacional, Escuela Nacional de Ciencias Biológicas, CD MEXICO, DF, MEX, 1950)
Various methods of studying the juvenility of the lymphocyte in normal and pathological conditions are compared Data are reported for the lymphocytic nuclear picture of Arneth, the lymphocyticnucleolar picture, The Rn index, and the internal structure of
BOL INST ESTUD MED BIOL
Keywords: ESTUDIO, MEDIOS, CUANTIFICACION, JUVENTUD, LINFOCITARIA; CIENCIAS MEDICAS; PATOLOGIA; PATOLOGIA CLINICA